Hubungan Pelaksanaan Fungsi Manajemen Kepala Ruangan dengan Motivasi Perawat Pelaksana di Ruang Rawat Inap RS Detasemen Kesehatan Tentara Bandar Lampung - Septi Rahmayani; Tri Adi Nugroho; Rizki Yeni Wulandari; Yunina Elasari (SEHATI: Jurnal Kesehatan, 2026)
The work motivation of implementing nurses is an important factor in determining the quality of nursing services in hospitals. However, problems are still found in the form of low work motivation characterized by a lack of discipline, work enthusiasm, appreciation, and unequal distribution of tasks. This condition is thought to be related to the suboptimal implementation of the ward head management function, including planning, organizing, directing, and controlling. This study aims to determine the relationship between the implementation of the ward head management function and the work motivation of implementing nurses in the Inpatient Ward of the Bandar Lampung Army Health Detachment Hospital. This study used a quantitative, correlative analytical design with a cross-sectional approach. The population and sample of the study amounted to 60 implementing nurses using a total sampling technique. Data collection was carried out using a questionnaire in September 2025, then analyzed univariately and bivariately. The results of the statistical test showed a p value = 0.007 (p 0.05), which indicates a significant relationship between the ward head management function and the work motivation of implementing nurses. Thus, it can be concluded that the effective implementation of ward head management functions is closely related to increased work motivation among nurses. Therefore, nurses are expected to continue to improve their work motivation through competency development, strengthening teamwork, and active participation in nursing activities